Gorlin-Goltz syndrome: A rare case report - Naveen N Kumar; S Padmashree; T R Jyotsna; Shilpa Padar Shastry (Wolters Kluwer Medknow Publications, 2018)
Gorlin-Goltz syndrome (GGS) is an autosomal dominant disorder with a high degree of penetrance and variable expressivity. It is a rare phakomatosis characterized by multiple odontogenic keratocysts (OKCs), bifid ribs, and other abnormalities. The incidence of the GGS is estimated at 1 in 57,000-1 in 256,000 in the general population. The OKC is frequently the presenting manifestation of this syndrome. We report a case of a 25-year-old male patient, presenting with a swelling in the right side of the face which was diagnosed as GGS by correlating the clinical findings, histological findings, and evaluating the various tools of imaging. In the case of GGS, it is of great importance to make an early diagnosis since the severity of complications such as maxillofacial deformities related to the jaw cysts can be avoided.